Factor XII Determinations in the Presence and Absence of Phospholipid Antibodies - Gallimore, M. J.; Jones, D. W.; Winter, M. (Thrombosis and Haemostasis, 1998)
Factor XII (FXII) levels were determined in plasma samples from 29 normal donors, 10 patients with inherited FXII deficiency (all lupus anticoagulant [LA] negative) and 67 LA positive patients, using clotting (FXIIct), chromogenic substrate (FXIIcs) and immunochemical (FXIIag) assays. Excellent correlations were obtained in the three FXII assays with the LA negative samples and between the FXIIcs and FXIIag assays in the LA positive samples. Correlations between both the FXIIcs and FXIIag with FXIIct in the LA positive patients were poor. Of 67 LA positive samples studied, 25 (37.3%) showed lower values in the FXIIct assay; 13 (19.4%) of these patients were pseudo FXII deficient with values of FXII below the lower limit of normal.These results indicate that a diagnosis of FXII deficiency can be made inappropriately in the presence of phospholipid antibodies and that such a diagnosis should not be made by FXIIct assay alone.